The effects of reboxetine on emotional processing in healthy volunteers: an fMRI study. - Norbury, R; Mackay, C; Cowen, P; Goodwin, G; Harmer, C (2008)
Recent neuropsychological studies in healthy volunteers suggest that antidepressants enhance the processing of positive emotional information. However, the neural substrates underpinning these changes have not been fully elucidated. The current study, therefore, used functional magnetic resonance imaging (fMRI) to map brain systems activated during successful categorization and subsequent recognition of self-referent positive and negative personality characteristics in healthy volunteers following short-term (7 days) repeated administration of the selective noradrenergic reuptake inhibitor reboxetine. Twenty-four healthy volunteers were randomly assigned to 7-day double-blind intervention with reboxetine or placebo. On day 7, neural responses during the categorization and subsequent recognition of positive and negative characteristics were assessed using fMRI. Questionnaires monitoring mood, hostility and anxiety were given before and during this intervention. During categorization, reboxetine was associated with greater activation to positive words, relative to negative words, in left precuneus and right inferior frontal gyrus. By contrast, at subsequent recognition reboxetine was associated with reduced response to positive words, relative to negative words, in left precuneus, anterior cingulate and medial frontal gyrus. These changes in the neural processing of positive and negative words occurred in the absence of significant differences in ratings of mood and anxiety. Such adaptations in the neural processing of emotional information support the hypothesis that antidepressants have early effects on emotional processing in a manner which would be expected to reverse negative biases in depression.